EFFECTS OF FOLIAR APPLICATION OF ORGANIC FERTILIZER "DISPER ALGHUM" AND GROWTH REGULATOR KT-30 ON CHEMICAL AND ENDOGENOUS HORMONE CONTENT OF APPLE TREES CV. "ANNA" - & Al.Bayati, Abd-Allatif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A factorial experiment within randomized complete block design (RCBD) was coducted during 2016 to investigate the influence of foliar application organic fertilizer "disper alghum" and growth regulator kt-30 on chemical content , endogenous hormone of young appel trees CV. "Anna". The trees were sprayed with organic fertilizer "disper alghum" was three levels (D) : (0 , 3 , 5 g.L-1) , and growth regulator KT-30 at four levels (K) : (0 , 5 , 10 , 20 mg.L-1) . Foliar application of organic fertilizer D5 (5 g.L-1) gave significantly higher values of the total chlorophyll content in leaves 291.0 mg.100g-1 fresh weight , percentage of nitrogen content in leaves 2.25 % , percentage of  phosphorus content in leaves 0.59 % , percentage of  potassium content in leaves 1.953 % , percentage of carbohydrates in the branches 8.377 % , and the ratio of carbohydrate to nitrogen in branches (C/N Ratio) 7.877 % , cytokinins materials like hormone in leaves 717.6 ppm , the percentage of nitrogen content in the branches showed significantly higher values in organic fertilizer D3 (3 g.L-1) 1.19 % . Foliar application of growth regulator K20 (20 mg.L) gave significantly higher values of the total chlorophyll content in leaves 327.4 mg.100g-1 fresh weight , percentage of  phosphorus content in leaves 0.618 % , percentage of  potassium content in leaves 2.039 % , percentage of carbohydrates in the branches 9.349 % , and the ratio of carbohydrate to nitrogen in branches (C/N Ratio) 7.818 % , cytokinins materials like hormone in leaves 847.5 ppm . K10 (10 mg.L) significantly incrase percentage of nitrogen content in leaves 2.30 % . There are non-significant value of percentage of nitrogen content in the branches all levels of growth regulator . The interaction treatment D5K20 significant increased total chlorophyll content in leaves , percentage of  phosphorus content in leaves , percentage of  potassium content in leaves , percentage of carbohydrates in the branches , cytokinins materials like hormone in leaves , other details are significant value in other interaction treatment non-control , there are non-significant value of percentage of nitrogen content in the branches in all interaction treatment of growth regulator